Drought Resistance Mechanism and Adaptation to Water Stress in Sorghum [Sorghum bicolor (L.) Moench] - Verma, Rajani; Kumar, Ramesh; Nath, Dr. Anamika (International Journal of Bio-resource and Stress Management, 2018)
Drought is a major constraint in sorghum production worldwide. Drought adversely affects growth and yield of crops to various extents. Growing of drought tolerant crops is a good option to obtain economical yields from water stress areas for which quick method to screen drought tolerant plants, particularly in early stages of their growth is important. Sorghum is one of the most important cereal crops and also the major staple food crop of millions of people in semi-arid tropics (SAT). Now-a-days, Sorghum grain is mainly used for human food, fodder, feed and fuel purposes. Moreover, seeds are used for popcorn and preparing delicious food. Sorghum is C4 plant which native to Sub-Saharan Africa.Drought-stress in sorghum has been characterized at both pre-flowering and post-flowering stages resulting in a drastic reduction in grain yield. Various drought-related traits, including root traits, leaf traits, osmotic adjustment capabilities, water potential, ABA content, and stability of the cell membrane, have been used as indicators to evaluate the drought resistance of plants. There are four different mechanisms which help in survival of plants under moisture deficit conditions viz., drought escape, drought avoidance, drought tolerance, and drought recovery. Drought stress can occur at any stage of crop growth ranging from seedling establishment, vegetative stage, panicle development post-flowering, period between grain filling and physiological maturity. Water stress responses in sorghum can be of physiological, morphological and phenological in nature.